2020
DOI: 10.1002/csc2.20015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mixed linkage β‐glucan quantitative trait loci and evaluation of AsCslF6 homoeologs in hexaploid oat

Abstract: Hexaploid oat (Avena sativa L.) is a commercially important cereal crop due in part to (1-3,1-4)-β-D-glucan (β-glucan), a hemicellulose important to human health. Cellulose synthase-like (Csl) genes have been shown to contribute to β-glucan production, with CslF6 likely being of major importance. Here, we report a genome-wide association study (GWAS) to identify quantitative trait loci (QTLs) controlling β-glucan production in oat. Three panels of elite accessions (Spring, Winter, and World Diversity) of oat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In the Kanota × Marion population, the Kanota alleles contributed increased kernel area and length but decreased beta-glucan. In the CORE association mapping panel, a QTL influencing β-glucan content (5.1; GMI_ES01_c13021_254) was detected at 135.5 cM [28], based on data from Aberdeen 2010, Fargo 2010 and Lacombe 2010 only. Rare allele homozygotes at avgbs_2_58834.1.20 (QBr%.CORE.6A) had higher percent broken groats compared with the common allele homozygotes (8.66% and 6.55%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the Kanota × Marion population, the Kanota alleles contributed increased kernel area and length but decreased beta-glucan. In the CORE association mapping panel, a QTL influencing β-glucan content (5.1; GMI_ES01_c13021_254) was detected at 135.5 cM [28], based on data from Aberdeen 2010, Fargo 2010 and Lacombe 2010 only. Rare allele homozygotes at avgbs_2_58834.1.20 (QBr%.CORE.6A) had higher percent broken groats compared with the common allele homozygotes (8.66% and 6.55%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As sequencing technologies have become more affordable, it is now feasible for many labs to map QTL for traits using a method called a genome-wide association study (GWAS) [ 8 , 9 , 10 ]. This method uses a large collection of markers to quickly scan a large number of subjects.…”
Section: Oat Grain Quality Information In the Graingenes Databasementioning
confidence: 99%
“…Over time, markers have evolved from being based on simple phenotypic characters, to using radioactive labor-intensive techniques, to using fast and inexpensive sequence-based approaches. While bi-parental mapping populations segregating for specific traits were most often used in the past [ 5 , 6 , 7 ], more recent studies often employ the use of association mapping panels comprising hundreds of different lines from different genetic backgrounds [ 8 , 9 , 10 ]. The CMap application [ 11 ] in GrainGenes provides a tool for the comparison of these datasets, thus enriching the marker density around genes in sparsely populated maps by virtue of common markers.…”
Section: Introductionmentioning
confidence: 99%
“…This gene family was subdivided into 8 gene groups designated CSLA to CSLH. The CSLF and CSLH groups were found only in cereals, [ 82 , 84 ] and the CSLF group was identified as a candidate for genes encoding β-glucans in cereal crops [ 78 , 85 , 86 ]. While studying the rice genome, six OsCslF genes belonging to the CSLF group were identified on chromosome 7, next to the Bmy2 marker.…”
Section: Regulatory and Structural Genes For The Biosynthesis Of Anthocyanins In Barley And β-Glucans In Oatsmentioning
confidence: 99%
“…Unlike diploid barley, oat is hexaploid and has three subgenomes: A, C and D. Subgenome-specific expression of homeologues A, C and D of the AsCslF6 gene showed that AsCslF6_C made the least contribution to β-glucan biosynthesis, while oat samples with a low β-glucan content demonstrated the highest input of the AsCslF6_C expression. At the same time, multiple homeologous copies of the AsCslF6_A and AsCslF6_D genes make a significant contribution to the common phenotype of samples with high β-glucan content [ 86 ].…”
Section: Regulatory and Structural Genes For The Biosynthesis Of Anthocyanins In Barley And β-Glucans In Oatsmentioning
confidence: 99%